A new species of Cymonomus A. Milne-Edwards, 1880, from the deep waters of the Gulf of Mexico (Crustacea: Brachyura: Cymonomidae) - Felder, Darryl L.; Tavares, Marcos (Zootaxa, 2024)
A new western Atlantic member of the cymonomid crab genus, Cymonomus A. Milne-Edwards, 1880, is described from the continental slope in the northern Gulf of Mexico. While the only two available specimens are poorly preserved and lack appendages, they are clearly distinct from other known members of the genus on the basis of the subangular anterolateral margin of the carapace paired with nearly straight, untapered eyestalks that terminate in a slightly bulbous, well-defined cornea, and antennal peduncles that reach beyond the second article of the antennular peduncle. Despite extensive collecting efforts in adjacent waters, the specimens remain known from only the type locality at 850 m depth.